Tasawuf dan Tantangan Perubahan Sosial - Yusno Abdullah Otta (Ulumuna, 2010)
Sufism in the eras of globalization and information often faces considerable challenges. The function and role of religion in modern life have in some aspects diminished, including sufism because it is claimed to have played no or less role in resolving problems nor stimulating social change. As one of Islamic traditions, sufism makes ihsan as its essential teaching. By this concept, sufism encourages humans to pray to God wholeheartedly. Sufism is now required to show its own existence and function by making fundamental contribution for modern life, an era which differ socio-culturally from the one when sufism firstly emerged. Sufism thus needs to adapt itself to the changes in the era of information and globalization so that it will remain relevant and suitable for human progress. Sufism needs to release itself from its exclusivism and to avoid being trapped in its own logic, namely speculative-trancendentalism